Improved Peritoneal Cavity and Abdominal Organ Imaging Using a Biphasic Contrast Agent Protocol and Spectral Photon Counting Computed Tomography K-Edge Imaging. Issue 10 (October 2018) - Si-Mohamed, Salim; Thivolet, Arnaud; Bonnot, Pierre-Emmanuel; Bar-Ness, Daniel; Képénékian, Vahan; Cormode, David P.; Douek, Philippe; Rousset, Pascal
Abstract : Objectives: To validate in vitro the capability of a high-spatial-resolution prototype spectral photon-counting computed tomography (SPCCT) scanner to differentiate between 2 contrast agents and to assess in vivo the image quality and the feasibility to image the peritoneal cavity in rats using the 2 contrast agents simultaneously within the vascular and peritoneal compartments. Materials and Methods: The authors performed SPCCT imaging (100 mAs, 120 kVp) with energy bin thresholds set to 30, 51, 64, 72, and 85 keV in vitro on a custom-made polyoxymethylene cylindrical phantom consisting of tubes with dilutions of both contrast agents and in vivo on 2 groups of adult rats using 2 injection protocols. Approval from the institutional animal ethics committee was obtained. One group received macrocylic gadolinium chelate intraperitoneal (IP) and iodine intravenous (IV) injections (protocol A, n = 3), whereas the second group received iodine IP and gadolinium IV (protocol B, n = 3). Helical scans were performed 35 minutes after IP injection and 20 seconds after IV injection. The SPCCT and contrast material images, that is, iodine and gadolinium maps, were reconstructed with a field of view of 160 mm, an isotropic voxel size of 250 μm, and a matrix size of 640 × 640 pixels using a soft reconstruction kernel. The SPCCT images were reconstructed with 2 different spatial resolutions to compare the image quality (sharpness, diagnostic quality, and organ visualization) of SPCCT (250 μm) with single-energy computed tomography (CT) (600 μm). Two radiologists evaluated the peritoneal opacification index in 13 regions (score = 0–3 per region) on each type of image. Concentrations of contrast agents were measured in the organs of interest. Results: In vitro, the concentration measurements correlated well with the expected concentrations. The linear regressions both had R 2 values of 0.99, slopes of 0.84 and 0.87, and offsets at −0.52 and −0.38 mg/mL for iodine and gadolinium, respectively. In vivo, the SPCCT images were of better diagnostic quality, with increased sharpness compared with the CT-like images ( P < 0.0001). Intraperitoneal diffusion was excellent, with similar peritoneal opacification index on SPCCT images and overlay of contrast material maps ( P = 1) without a significant difference between protocol A (37.0 ± 1.7) and protocol B (35.3 ± 1.5) ( P = 0.34). Only the contrast material maps demonstrated clear visual separation of the contrast agents, allowing specific quantification of the physiological enhancement in the liver, spleen, and kidney and the urinary clearance in the renal pelvis and bladder. Renal excretion of the contrast agents injected IP was observed and was consistent with blood diffusion. Conclusions: Spectral photon-counting CT can be used to perform a complete peritoneal dual-contrast protocol, enabling a good assessment of the peritoneal cavity and abdominal organs in rats. Abstract : Supplemental digital content is available in the text.